Plan de marketing para la ferretería y repuestos de motos “JP” en el cantón Mocache, año 2015 - Montalván Tarira, Luisana María (2015)
In the present study a marketing plan was set for an ironmongery and motorbike parts store "JP" in Mocache, this company has been established for many years and has a good market in the ironmongery and motorbike parts field in Mocache. That company “JP” wants to increase its market through a marketing plan that permits to enlarge its coverage and participation with the competition, and enable the company to have a strong position with excellent quality products. In chapter one, it analyzes the contextualization, by analyzing the current situation of the company “JP”, through a diagnosis that identified the causes and effects that make it possible the problematization, and explaining the importance of the rationale and objectives approach . In Chapter two, it details the conceptual and referential framework discussed by reviewing books, textbooks, magazines, internet, which provided relevant and necessary concepts to meet the objectives in research theories. In chapter three, types, technical methods, primary and secondary sources of information, population and sample, instruments were identified which were used for the implementation of surveys to the population of Mocache related to the ironmongery to know its market positioning. In Chapter four, it reflects the results obtained during the investigation in which the analysis of the situation of the company “JP” demonstrates that it does not have the vision, mission and strategic values, which prevents the ironmongery to achieve a greater market positioning in the target. In addition, the market research determined that there is a high demand of ironmongery products and motorcycle parts. It is also important to implement marketing strategies that will enable the company to raise its market position and thus improve its profitability. In chapter five, expected results and recommendations are due. Finally, in chapter six, it reflects the consulted and necessary literature to meet the objectives of this study.